The Middle Paleolithic revolution, the origins of art, and the epistemology of paleoanthropology - Zilhão, João (2021)
Gilman (1984) proposed that an "Upper Paleolithic Revolution" triggered by technological progress and demographic growth, and standing for the emergence of ritual reciprocity mechanisms, explained the major behavioral innovations se en in Europe after 40,000 years ago. Subsequent developments have shown that the notion remains valid but that early manifestations of those behaviors can be se en in the archeological record since at least the beginning of the Last Interglacial, and across the Old World. Thus, the process that brought a world of many, diverse, ethnically bounded Humanities out of the womb of the unbounded single Humanity of earlier times was rather more gradual and longer; the beginning of the Middle Paleolithic/Middle Stone Age was the initial stage of such a revolution, the beginning of the Upper Paleolithic was the lasto The finding that, in Neandertal Iberia, cave art dates back to >65,000 ago has been key to this reassessment of the Middle-to-Upper Paleolithic transition and, not unexpectedly, underwent sorne questioning. The arguments used, devoid of empirical basis as they are, highlight the extent to which the debate of Paleoanthropology's "Big Issues" is biased by often implicit, obsolete assumptions inherited from the origins of the discipline and by the social! cultural context of knowledge production.